2015
DOI: 10.11113/jt.v74.3009
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Erosion Measurement Along Tanjung Lumpur to Cherok Paloh, Pahang During the Northeast Monsoon Season

Abstract: The map of Tanjung Lumpur to Cherok Paloh from 1996 to 2004 revealed that there were significant changes on coastal profiles. If the problem remains unsolved within 5 to 10 years, the beaches in the area might be fully eroded. The main objective of this study is to measure erosion of the coastline along Tanjung Lumpur to Cherok Paloh, Pahang during the northeast monsoon (December 2013 to February 2014). Transit set and dry sieving method were used for beach profile and grain size characteristics measurement. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…The changing patterns of shoreline for both areas showed a very active process of erosion. This is consistent with the shoreline erosion findings of Azid et al (2015), which showed that Tanjung Lumpur to Cherok Paloh of Pahang coasts had significant changes of the coastal shorelines between 1996 and 2004. Coastal areas of Pantai Cherating, Legend Villa Resort and Sungai Ular were found to show a minimum amount of shoreline eroding consisting of 0.1 to 0.5 ha while Pantai Balok, Kelab Golf Pahang, Taman Gelora and Pantai Sepat did not have any accretion process along the shorelines.…”
Section: Monitoring Of Shoreline Changessupporting
confidence: 91%
See 1 more Smart Citation
“…The changing patterns of shoreline for both areas showed a very active process of erosion. This is consistent with the shoreline erosion findings of Azid et al (2015), which showed that Tanjung Lumpur to Cherok Paloh of Pahang coasts had significant changes of the coastal shorelines between 1996 and 2004. Coastal areas of Pantai Cherating, Legend Villa Resort and Sungai Ular were found to show a minimum amount of shoreline eroding consisting of 0.1 to 0.5 ha while Pantai Balok, Kelab Golf Pahang, Taman Gelora and Pantai Sepat did not have any accretion process along the shorelines.…”
Section: Monitoring Of Shoreline Changessupporting
confidence: 91%
“…Coastal areas in Pahang offer many beautiful beaches with fascinating landscape and scenery, which capture the attention of visitors and tourists. Cherating, Teluk Chempedak, Tanjung Lumpur and Pantai Sepat are the most attractive beaches in Pahang, which attract people for recreational activities (Azid et al 2015;Tobergte & Curtis 2013). Malaysia's coastline is over 4,809 km where more than 1,300 km of Malaysian beaches are experiencing erosion (Ong 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The sedimentation problems is the build-up (aggradation) of sediment on the land surface or the bed of a watercourse. The sediment production in drainage systems and in river leads will be rising the bed levels and caused the flash floods phenomenon during heavy rainstorms [18]- [20], [31], [32]. The physical characteristic recapitulation of sediment ponds below is a dynamic process and is dependent upon the geomorphic and hydraulic characteristics of the drainage system.…”
Section: Weir Widthmentioning
confidence: 99%
“…In order to preserve coastal groundwater, the sources of saline water and mechanisms of mobility need to be identify so that, fresh groundwater resources can be sustained [10]. Three common methods used for water quality assessment in coastal areas are hydrogeochemical methods, geophysical investigations and multivariate technique [8,11]. In this study, hydrogeochemical method is adopt to understand the hydrochemical temporal variations, so that the potential contamination of saltwater into coastal groundwater can be identified.…”
Section: Introductionmentioning
confidence: 99%